2019
DOI: 10.1186/s10086-019-1834-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of visual stimulation with full-scale wall images composed of vertically and horizontally arranged wooden elements

Abstract: Wood is a raw material that is used not only in the production of structural members for various buildings, but also in the interior finishes that are directly seen and touched by the occupants. Wood has also been recognized as a humanfriendly material, but few studies have experimentally confirmed the physiological benefits it brings to humans. Therefore, the aim of the present study was to investigate the physiological effects of visual stimulation with wood. Two types of full-scale square, wooden-wall image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Four experiments are characterized by short exposure times to wood (90 s) and low numbers of participants (between 14 and 28), 34,4750 while the other five studies employed longer exposure times (10–75 min) and typically larger number of participants (between 12 and 119). 35,36,45,46,51,52 Five studies created wooden settings of only light colour wood, 35,36,45,47,48 two studies used only dark wood, 34,49,50 and two studies employed both light and dark wood, either separately in different settings or combined in the same room. 46,51,52 Five studies included solid wood, 35,4852 three used wood composites 34,36,46 and one used images of wood.…”
Section: Resultsmentioning
confidence: 99%
“…Four experiments are characterized by short exposure times to wood (90 s) and low numbers of participants (between 14 and 28), 34,4750 while the other five studies employed longer exposure times (10–75 min) and typically larger number of participants (between 12 and 119). 35,36,45,46,51,52 Five studies created wooden settings of only light colour wood, 35,36,45,47,48 two studies used only dark wood, 34,49,50 and two studies employed both light and dark wood, either separately in different settings or combined in the same room. 46,51,52 Five studies included solid wood, 35,4852 three used wood composites 34,36,46 and one used images of wood.…”
Section: Resultsmentioning
confidence: 99%
“…Its portable (in some models), less noisy, and less bodily constraining characteristics have made it the most common technique used by researchers to investigate the "online" brain activity during contact with nature. Employing fNIRS, previous studies have reported that viewing forest landscapes [16] or foliage plants [17]; viewing images of forests [18], garden landscapes [19], or a wooden interior wall [20,21]; smelling Japanese cypress leaf oil/air or Japanese cedar chips (for a review, [10]); touching a natural pothos leaf (Epipremnum aureum, [22]) or solid wood [23,24]; or transferring foliage plants [25] reduces the concentration of oxy-Hb in the prefrontal cortex (PFC). This has been interpreted as a calming or relaxing effect on the brain, which underlies many of the affective benefits or mood-improving effects achieved by contact with nature.…”
Section: Introductionmentioning
confidence: 99%
“…Adult women in their 20 s were included with consideration of continuity with our previous research [18][19][20][21][22][23][24][25][26][27]31] on the effect of wood-derived stimuli on the physiological responses in humans. In addition, visual stimulation, study protocol, physiological measurements, psychological measurements, and statistical analysis in the study of Nakamura et al [31] were applied in the current investigation. Their research revealed the physiological effects via a vision when using images of a full-scale wall made up of horizontally and vertically arranged wooden elements on prefrontal cortex activity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, changes in the percentage of wood caused differential physiological changes, and visual stimulation in a room comprising 30% wood, a standard type of living room commercially available in Japan, induces a physiological relaxation effect. Recently, Nakamura et al [31] examined the effects of visual stimulation using two full-size square mural images arranged vertically and horizontally as well as knot-free clear wood on brain and autonomic nervous system activities among young women in their twenties. Results showed that visual stimulation using mural images arranged vertically and horizontally, compared with gray wall images, significantly decreased left and right prefrontal oxygenated hemoglobin concentrations.…”
Section: Effects Of Nature-derived Visual Stimuli Such As Wood On Hummentioning
confidence: 99%
See 1 more Smart Citation